APPLICATIONS TO MANAGEMENT OF HARD SKILL AND SOFT SKILL LIBRARIES TO REALIZE THE IMPLEMENTATION OF PRIMARY SERVICES IN HIGHER EDUCATIONAL LIBRARY IN THE SOCIETY ERA 0.5 IN ORGANIZATIONAL PSYCHOLOGICAL PERSPECTIVE - BAKHTIYAR (CV KULTURA DIGITAL MEDIA, 2022)
Libraries in the digitalization era should be equipped with renewable information and communication technology. There has been an explosion and explosion of information, creating a need for information for the